Soil carbon sequestration in the NDCs: Contributions from Brazil - Marzall, Katia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Presentation by Katia Marzall, Coordinator for Climate Change and Agriculture at the Ministry of Agriculture, Livestock and Food Supply in Brazil. The presentation was part of the Webinar on Soil carbon in the Nationally Determined Contributions hosted by CCAFS, the German Ministry of Food and Agriculture, and the 4 Per Mille Initiative and held on Earth Day, 22 April 2020.